Expression of "Sack" Basic Units in Uzbek People's Proverbs - Kamola Rikhsiyeva (International Journal on Integrated Education, 2022)
The semantic aspects of the expression of the unit "sack" in Uzbek folk proverbs are examined in this article. Proverbs are explained in terms of their location, function, and semantics. In dictionaries, the origin, base, construction, and semantic growth of such lexemes are investigated. The meanings of the Uzbek language in the explanatory and etymological dictionary are investigated, and the participation in the articles is analyzed on the basis of this information. The items are grouped into groups and their definitions are discussed, all of which are based on the "sack" units.